Kolaborasi Guru dan Orang Tua dalam Mengatasi Perilaku Menyimpang pada Siswa - Rindra Risdiantoro (PRODI BIMBINGAN KONSELING ISLAM INSTITUT AGAMA ISLAM SUNAN KALIJOGO MALANG, 2021)
Abstract. One of the controllers of children's delinquency is teachers and parents. They are the main controllers to protect and save individuals and groups from deviant behavior. Efforts made by teachers and parents to their children who commit deviant behavior at MI Darul Hikam Batu City by making efforts to prevent (preventive), inhibit (responsive), repair (rehabilitation) and cure (curative). The objectives of this study are: 1) to explain the behavioral deviations carried out by students of MI Darul Hikam Batu City, 2) to explain the factors that cause deviant behavior to students at MI Darul Hikam Batu City, 3) to explain the collaboration of teachers and parents in overcoming deviant behavior. to the students of MI Darul Hikam Batu City. The form of deviant behavior carried out by students at MI Darul Hikam Batu City is included in the category of deviation from social norms. The factors that cause deviant behavior in Darul Hikam MI students in Batu City are the social environment, lack of attention from parents, lack of discipline, being influenced by electronic media or social media. Collaboration between teachers and parents in overcoming the deviant behavior of MI Darul Hikam students in Batu City through reprimands, warnings, advice, and punishments. Keywords: collaboration, teachers and parents, deviant behavior.